THE IMPACT OF USING QUIZLET-BASED PBL MODEL ON GLOBAL DIVERSITY IN ELEMENTARY SCHOOLS - Angelina, Tiara; Qurrotaini, Lativa (JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
This research examines how the Quizlet application and the PBL model can improve elementary students’ understanding of cultural diversity. The research targets the low level of global diversity awareness among 5th-grade students at SDN Sudimara 1 Tangerang despite implementing the Merdeka Curriculum. An experimental method was employed, using a Non-Equivalent Control Group Design with two student groups: a control group using traditional teaching methods and an experimental group utilizing Quizlet alongside the PBL paradigm. Researchers collected data through observations, interviews, and tests, including pretests and post-tests. The findings showed that the experimental group’s average post-test score was higher than the control group’s. The experimental group achieved an average post-test score of 84.48, while the control group reached an average of 73.08, a difference of 11.4 points. Additionally, the experimental group improved its average score from 66.04 to 84.48, whereas the control group increased from 58.44 to 73.08. The results indicate that the PBL model supported by Quizlet can help students understand global diversity better. According to this research, using the Quizlet application with the PBL paradigm can raise educational standards and enhance elementary students’ awareness of cultural diversity. Implementing this model in the educational process enables students to gain a deeper understanding of cultural diversity and fosters a stronger desire to learn.